JILBAB ANTARA ORISINALITAS DAN PRODUK BUDAYA (PERSPEKTIF AL AS{I - Ainur Rohim (JUPE : Jurnal Pendidikan Mandala, 2022)
The background of the research departs from the phenomenon of the rejection of some Muslim women against the 3 Ministerial Decree, precisely on 07 February 2021, which is trending and viral in the world of social media because it requires all students to wear the hijab, and Muslim women who refuse it are psychologically pressured until someone wants to kill.  Themselves because they are judged, marginalized and stigmatized as immoral women.  This paper is expected to provide a holistic and relevant answer so that it can be used as a basis for an objective and proportional attitude towards women who wear the hijab or those who do not.  The research includes library research that uses the Mawd{u>i> method in the perspective of Al As{il Wa Al-Dakhi<l Fi< Al Tafsi<>r.  From the research, it can be stated that the hijab is a civilization and a product of human culture that existed long before the Samawi religions came and then Islam came to formulate and legalize the hijab into shari>ah.  The law of wearing the hijab according to classical scholars is obligatory while contemporary scholars consider that wearing the hijab is only a recommendation (Maw'iz{ah) not Tashri>'.  It should be noted that a woman's piety cannot be measured and measured from her hijab, although ideally a woman should dress modestly and have noble and virtuous character.